2022
DOI: 10.1007/s40273-022-01181-3
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Value-Based Price of a Multi-Cancer Early Detection Genomic Blood Test to Complement Current Single Cancer Screening in the USA

Abstract: Background Multi-cancer early detection (MCED) testing could increase detection of cancer at early stages, when survival outcomes are better and treatment costs are lower, but is expected to increase screening costs. This study modeled an MCED test for 19 solid cancers in a US population and estimated the potential value-based price (the maximum price to meet a given willingness to pay) of the MCED test plus current single cancer screening (usual care) compared to usual care alone from a third-party payer pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…In addition, the advent of liquid biopsies may eventually provide a mechanism for annual screening for all cancers. Although these tests are in their infancy, not widely available, and it is uncertain whether they will become cost efficient for standard testing, they have the potential increase early detection of breast cancer in men 52–54 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the advent of liquid biopsies may eventually provide a mechanism for annual screening for all cancers. Although these tests are in their infancy, not widely available, and it is uncertain whether they will become cost efficient for standard testing, they have the potential increase early detection of breast cancer in men 52–54 …”
Section: Discussionmentioning
confidence: 99%
“…Although these tests are in their infancy, not widely available, and it is uncertain whether they will become cost efficient for standard testing, they have the potential increase early detection of breast cancer in men. [52][53][54] Retrospective, population-based studies using cancer registry data have limitations.…”
Section: Indicates Charlson Comorbidity Indexmentioning
confidence: 99%
“…From a technical standpoint, based on the experience from this study and foreseeable optimizations, we expect a throughput of 100 patient samples per day per UHPLC-MS/MS instrument at a cost per sample <$50. This cost is 5-10 times lower than a previous estimate for a cfDNA/ protein-based MCED test (8) and well below its presumed health economics value of ~$1200 (31). The final cost depends on whether the free GAGome MCED test requires one (urine or plasma) or two samples (both urine and plasma) per patient.…”
Section: Discussionmentioning
confidence: 74%
“…Of these, 26 were initially detected by blood testing. Although this study found the MCED test to be far from ideal on its own, in combination with diagnostic imaging, it could improve early cancer detection [58 ▪▪ ]. The addition of an annual MCED test would cost $5421 for patients and is predicted to provide 0.34 years of quality-adjusted life for a single person.…”
Section: Current Topography Of Biomarker-driven Technologiesmentioning
confidence: 90%